KONSTRUKSI PRAKTIK SISTEM PENGENDALIAN MANAJEMEN MODEL PESANTREN SALAFIYAH - Falah, Syaikhul (BISNIS, 2014)
The focus of this study is to provide an understanding of the practice of management control systems in pesantren salafiyah. This study tries to provide an understanding of the practice of management control system from the perspective of social construction and Weberian charismatic leadership approach in pesantren salafiyah. Qualitiatif methods use a combination of the two methods through research; ethnographic and case studies selected as a research strategy. Location of research is pesantren (API) Tegalrejo Magelang. Data was collected through in-depth interviews, participant observation, and documentation. The results externalization, objectivation and insternalization held in reverence gave birth to a boarding API students against clerics who reflect management control system. Reverence is an important value for the creation of a stable social relationships within pesantren salafiyah.